Does Benford's law hold in economic research and forecasting? - Stefan Günnel; Karl-Heinz Tödter (Deutsche Bundesbank, 2007)
First and higher order digits in data sets of natural and socio-economic processes often follow a distribution called Benford's law. This phenomenon has been used in many business and scientific applications, especially in fraud detection for financial data. In this paper, we analyse whether Benford's law holds in economic research and forecasting. First, we examine the distribution of leading digits of regression coefficients and standard errors in research papers, published in Empirica and Applied Economics Letters. Second, we analyse forecasts of GDP growth and CPI inflation in Germany, published in Consensus Forecasts. There are two main findings: The relative frequencies of the first and second digits in economic research are broadly consistent with Benford's law. In sharp contrast, the second digits of Consensus Forecasts exhibit a massive excess of zeros and fives, raising doubts on their information content.
Keywords: C12; C52; C8; 330; Benford's Law; fraud detection; regression coefficients and standard errors; growth and inflation forecasts; Wirtschaftsforschung; Publikationsanalyse; Wahrscheinlichkeitsrechnung; Konjunkturprognose; Ökonometrie; Theorie; Welt